Methodological proposal for the evaluation of community tourism, case study in Arajuno, Pastaza - Ortega Ocana, Angel Fernando (2013)
The community tourism is one of the activities which route to sustainable develop- ment of populations that have valuable natural assets. Between 2011 and 2012 was an increase of the touristic activity around 9 % of visitors in Ecuador, an increase that is maintained so far in 2013, represents the sixth item of foreign exchange earnings from products or services in the Ecuadorian economy after oil exports, bananas, shrimp and derivatives. In 2002 the community tourism caught the 3,67 % of the total revenue generated by tourism. In the Pastaza province due to the presence of seven nationalities ( Kichwa, Shuar, Achuar, Huaorani, Andoa, Zápara Shiwiar ) have led to the generation of products under the approach of the community tourism, because of the natural and cultural features it presents. The methodological proposal evaluation is based on case of studies of communities living in the canton Arajuno in the Pastaza province, covering the analysis of two components: tourist characteriza- tion Community Tourist Operation (CTO), and characterization of attractions and/or tourism resources operations of thirteen community operations. This information that allows the public, private and community decision – making, and generating information for academic purposes, taking into account that such offer is based on three factors: respect for the natural and cultural environment, integral sustainability, and effective control tourism business by the direct benefits for communities.